+0  
 
+1
367
1
avatar

Solve using elimination.

-10x + 3y = 1

-8x + 3y = 5

Guest Apr 19, 2017
 #1
avatar+91160 
+1

 

-10x + 3y  =  1       multiply through by -1   =  10x - 3y = -1   (1)

-8x + 3y   =  5       (2)

 

Add  (1)  to (2)   

 

2x  =   4      divide both sides by 2

x  = 2

 

Sub this into  (1)  to find y

 

10(2)  - 3y   =  -1

20  - 3y   =  -1       subtract 20  from both sides

 

-3y   =   -21         divide both sides by -3

 y  =  7

 

So   (x,y)   =  (2, 7)

 

 

 

cool cool cool

CPhill  Apr 19, 2017

11 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.